Enhancing workforce efficiency in construction: a technological intervention for skill matching and resource optimization using extreme programming - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research addresses a crucial issue related to labor deployment and management in construction project management. In the context of the complexity of skill needs and dynamic changes in construction projects, this research proposes an innovative solution by developing a Human Resource Management application. The research method was structured in three main stages. The first stage involved data collection to identify skills needs, team dynamics, and project demands. The second stage involved developing the application using the Extreme Programming (XP) method, focusing on critical features such as skills matching, team performance monitoring, and labor risk analysis. The final stage was user acceptance analysis, where a user acceptance measurement model was applied to a representative group of users. The results showed that the application received high user ratings, with the Interactive Project Schedule feature being the most favored. Team Performance Monitoring and Centralised Team Communication also received high ratings. While Labour Risk Analysis scored positively, there were notes for improvement. The app provides an integrated solution for effective human resource management in construction projects. The main contribution of this research lies in developing an application that is responsive and adaptive to changing project needs, utilizing XP principles.